Considering sport for development and peace through the capabilities approach. Issue 1 (2nd January 2017) - Darnell, Simon C.; Dao, Michael
Abstract: Heeding calls to integrate international development studies with Sport for Development and Peace (SDP), we approach SDP using the Capabilities Approach as articulated by Martha Nussbaum. Applying such a framework to the study and practice of SDP offers a politically engaged yet practical approach, and serves to theorise ways in which sport programmes might be conceptualised and organised as part of holistic approaches to development and not simply instruments thereto. While a number of criticisms of the Capabilities Approach are discussed, we ultimately advocate for its critical deployment within the ongoing study and practice of SDP.